Chemotherapy and Heart-Specific Mortality in Elderly Men with Prostate Cancer: A Propensity Score Matching Analysis - Chenghao Zhanghuang; Huake Wang; Jinkui Wang; Li Li; Jinrong Li; Zipeng Hao; Jiacheng Zhang; Ling Liu; Bing Yan (PLoS ONE, 2025)
Objective Prostate cancer (PC) is the most common malignant tumour in men, and atherosclerotic cardiovascular disease (ASCVD) is the leading cause of non-cancer death in PC patients. The main purpose of this study was to investigate whether chemotherapy increases heart-specific mortality (HSM) in elderly patients with PC. Methods Patient information was downloaded from the Surveillance, Epidemiology, and End Results (SEER) database from 2010 to 2018. We included all elderly patients with PC. The multivariate logistic regression model was used to explore the influencing factors of patients receiving chemotherapy. Confounders were excluded using a 1:1 proportional propensity score match, and a competing risk model and cumulative incidence plot were used to analyze HSM and other cause mortality (OCM) in patients who received chemotherapy versus those who did not. Results A total of 135183 elderly prostate patients were enrolled in this study, of whom 1361 received chemotherapy. The multivariate logistic regression model showed that older patients were more likely to not receive chemotherapy, married patients were more likely to receive chemotherapy, and the higher the TNM stage and tumor histological grade, the more patients received chemotherapy. In the original cohort before unmatched, there was no significant difference in HSM between chemotherapy and non-chemotherapy patients (P = 0.27). After 1:1 matching, HSM was significantly higher in patients without chemotherapy than in patients with chemotherapy (HR 2.54; P =0.002). Conclusions Our results indicate that HSM is significantly higher in patients without chemotherapy than in those with chemotherapy. Therefore, although chemotherapy can lead to cardiotoxicity in elderly patients with PC, chemotherapy does not increase the HSM of patients and will benefit patients in the long-term survival.